Realising holistic creative thinking through seven principles: a 21st century paradigm leading to sustainable innovation. (11th January 2023) - Khandelwal, Nishant; Mehta, Anil
The current business world and the academic fraternity agree on the need for creative thinking and innovation in every sphere of life to ensure global sustainability. Today, we are forced to provide those innovative solutions which are sustainable, i.e., one which caters to the social and environmental needs of both the current and future generations, besides aiming at profitability. To meet such a challenge, one needs a different paradigm. This paper, proposes a holistic set of seven principles for practice of management for problem solving and innovating through creative thinking. Together, these principles provide holistic creative thinking resulting into sustainable business and social innovations if taken up to their conclusions, given any target or challenge. Since these are principles, they are fundamental, enduring and universally applicable. The purpose of this paper is to help both individuals and organisations in setting and achieving their goals pertaining to creative thinking and sustainable innovation.